The stuff of soldiers a history of the Red Army in World War II through objects - Schechter, Brandon M (Ithaca [New York] [u.a.] : Cornell University Press, 2019)
"This book tells the story of the Great Patriotic War via objects from spoons to tanks. It was the uniform world of material goods that united diverse soldiers in the ranks of the Red Army and was often all that separated civilians from soldiers"
Literaturverzeichnis S. 249 - 305
Keywords: Sowjetunion; Raboče-Krestjanskaja Krasnaja Armija; Russlandfeldzug <1941-1945>; Sachkultur